AFRICA VIEWED THROUGH ITS PROVERBS AND LITERATURE - Ana Cristina Pinheiro Fortes (European Scientific Journal, ESJ, 2014)
This paper aims at demonstrating that a better and richer analysis of a literary work can be realized if a deep exam of the proverbs used is carried out. This work has a semiotic rather than a linguistic perspective as we try to throw light on the world-view of the people the literary text refers to. The work is divided into two chapters. In Chapter 1 we give a bird´s eye view of African proverbs and their use in African literature, and in Chapter 2 we focus on Chinua Achebe´s masterpiece Things Fall Apart. We have adhered to Bhuvaneswar´s classification of proverbs into prototypical, vehicle and contextual so as to carry out a semiotic analysis of the proverbs used by Chinua Achebe.